Metody psychologiczne w prawie : szkic problemu - Helios, Joanna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
This paper aims to present research approaches in psychology and their possible application to law. In the author’s view, there is no such thing as a single psychological research approach. On the contrary, there are many research approaches, due to thefact that psychology as a science is developing rapidly and new approaches are constantly emerging (e.g. neuropsychology). Meanwhile, jurisprudence distinguishes a psychological research approach linked to the school of legal realism, especially the European school and the concept of Leon Petrażycki.
Keywords: metody psychologiczne; prawoznawstwo; emocje; neuronauka; psychologia prawa